GAMBARAN GEJALA PERNAFASAN PADA PEKERJA BAGIAN QUALITY CONTROL PABRIK PENGOLAHAN CRUDE PALM OIL (CPO) PT.SMART,TBK DI BELAWAN TAHUN 2013 - Rizka Wita; Lina Tarigan; Halinda Sari Lubis (Lingkungan dan Kesehatan Kerja, 2013)
Respiratory symptom description of Quality Control workers in crude palm oil processing plant PT. Smart Tbk Belawan on 2013. Occupational disease can decrease the health and welfare degree of workers, one of causes factor is chemical. The quality control workers always use chemical which corrosive and irritant to the respiratory system. The method of this research is descriptive survey research. Population is all of quality control workers totaling 36 person. Sample used is the total population. The result of this research showed that a total of 30 workers (83,4%) aged ≤ 31 years, there were 24 workers (66,7%) had a mild respiratory symptom. In 6 workers aged > 31 years, there were 3 workers (8,3%) had a mild and severe respiratory symptom. In 31 workers (86,1%) have worked for ≤ 10 years, there were 25 workers (69,4%) had a mild respiratory symptom. In 5 workers (13,9%) have worked for > 10 years, there were 2 workers (5,6%) had a mild respiratory symptom and 3 workers (8,3%) had a severe respiratory symptom. In 20 workers (55,6%) who always used mask while working, there were 15 workers (41,7%) had a mild respiratory symptom. In 16 workers (44,4%) who rarely used a mask while working, there were 12 workers (33,3%) had a mild respiratory symptom and 3 workers (8,3%) had a severe respiratory symptom. Based on the result, company should provide the respiratory personal protective equipment which appropriate for using chemical, and the workers should always use it as prevention of respiratory diseases. Keywords : respiratory symptom, chemical, workers, quality control